Reading Comprehension Assisting Children with Learning Difficulties - Woolley, Gary.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
Reading Comprehension: Assisting Children with Learning Difficulties examines the complex nature of reading comprehension. It introduces a model for classifying reading comprehension based on an expanded Simple View of Reading. Issues related to assessment, diagnosis, and remediation of reading comprehension difficulties are discussed and translated into clear recommendations to inform reading intervention design and practice. It gives an informed understanding as to why reading comprehension is difficult for some children with learning disabilities such as ADHD, autism, language difficulties and dyslexia. From leading literacy research, the book develops a deeper understanding of thinking processes that facilitate comprehension at the word, discourse, and metacognitive levels. Children will benefit from the introduction of evidence-based methods for teaching reading comprehension using structured multiple-strategy frameworks.
Introduction -- Reading Difficulties -- Reading Comprehension -- Cognitive Architecture -- Language Processing -- Word Level and Discourse Processing of Text -- Visualisation -- Using Inferences and Strategic Processing -- Dynamic Processing in and Between Texts -- Motivation -- Self-regulation, Metacognition, and Engagement -- Comprehension is Strategic -- Multiple Strategy Frameworks -- Supporting Learning -- Assessment and Comprehension -- References -- Subject index.
Keywords: Education; Educational tests and measurements; Literacy; Education; Literacy; Learning & Instruction; Assessment, Testing and Evaluation